Potential use of Oncostatin M in Critically ill Patients with acute Kidney Injury - Soliman, Amin; Selim, Nora Mahmoud Ali; Abdel-Motelb, Motaz Esam El-din; Darwish, Rasha Ahmed; Soliman, Ahmed (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Acute kidney injury (AKI) is one of the most common complications affecting patients admitted to intensive care unit (ICU) worldwide. In response to injury, both kidneys and liver secrete acute phase reactants as a mechanism of protection. Oncostatin M (OSM) is a member of the interleukin-6 family of cytokines which was found to be elevated during renal injury as in diabetic nephropathy, glomerulonephritis, and obstructive nephropathy. AIM: The study aimed to assess the role of OSM as an early biomarker of AKI in critically ill patients. PATIENTS AND METHODS: We conducted a prospective case–control study that included 202 patients admitted to ICU within Kasr El-Aini University hospitals during the period between January 2022 and August 2022. Eligible patients were divided into two groups according to the occurrence of AKI, and Oncostatin was assessed in the sera of the included patients. RESULTS: Our findings showed that the AKI group had statistically significant lower OSM levels compared to the control group, especially among those patients who had poor clinical outcomes and non-survivors. We also found that OSM is a good predictive tool for the prediction of mortality among patients admitted to ICU with sepsis complicated with AKI (Area under the curve = 0.673, 95% confidence interval: 0.532–0.814) with a sensitivity of 83.8% and specificity of 61.4%. CONCLUSION: OSM plays an important role among critically ill patients who are admitted to the ICU with sepsis, it can significantly predict AKI development and subsequent mortality.